Spyware-Based Keylogger Design for Monitoring Smartphone User Activities Using the Smart Keylogger Application: Perancangan Keylogger Berbasis Spyware untuk Memonitoring Aktivitas Pengguna Smartphone Menggunakan Aplikasi Smart keylogger - Sari Wulandari (Progressive Information, Security, Computer, and Embedded System, 2024)
The era of growing information technology has led to increasing threats to the security and privacy of computer and mobile device users, such as data theft and unauthorized use. In addition, the use of the internet by children and adolescents also requires special supervision. Therefore this research contributes to the use of the smart keylogger application as an effective solution for monitoring smartphone user activity and protecting user data security and privacy, especially in use by children and adolescents. The research method used is experimental research, in which a smart keylogger application is installed on a user's smartphone to monitor user activity over a certain period. The results of the study show that the smart keylogger application runs well in the background of the device, recording every keystroke the user makes, including internet browsing history and other activities. Overall, this spyware-based smart keylogger application is an effective solution for monitoring smartphone user activity, protecting data security and privacy, and providing more effective monitoring of internet use by children and adolescents.